Literature Review: Identification of Research Trends on Misconceptions in Physics Material in 2019-2024 - Istiqomah, Rofita; Subali, Bambang (Universitas Tidar, 2025)
Misconception is one of the main problems and continues to appear in physics learning. This investigation adopts the Systematic Literature Review technique, in accordance with the PRISMA standards and includes literature data spanning the period from 2019 to 2024. The sample used amounted to 64 scientific articles from journals that were searched through the Publish or Perish software with the Google Scholar, Scopus, Semantic Scholar, and Crossref databases. This study aims to identify and examine research trends regarding student misconceptions in physics materials in the 2019-2024, misconception diagnostic methods, physics concepts that are most commonly misconceived, factors that cause misconceptions, and strategies that can be used to overcome misconceptions in physics materials. This research procedure uses the PRISMA guided framework, which includes identification, screening, eligibility, and included. This study's results demonstrate that exploring student misconceptions in physics continues to be a significant focus in current research which can be seen from the fluctuating number of publications and the increasingly diverse methods of diagnosis and media used in research. It was found that the most student misconceptions occurred in kinematics material on the concept of straight motion and projectile motion with the dominant factor causing misconceptions coming from within students themselves.